Identidad social de una persona transgénero masculina posterior a la Mastectomía (2024)
The research focuses on the construction of the social identity of a transgender man who has undergone a mastectomy. Using a qualitative approach and semi-structured interviews, the experiences and perceptions of the participant are explored, allowing for a deeper understanding of his reality and the factors influencing his social identity. The importance of social support in the process of personal acceptance is highlighted, where validation of identity by friends, family, and colleagues is fundamental. Despite significant physical changes, many transgender men feel the need to moderate their expression to conform to social norms. However, it is observed that, despite barriers and negative perceptions, many develop resilience and self-confidence, enabling them to renegotiate their identity in different environments.